SMOKING STATUS AFFECTING SURVIVAL OF ADENOCARCINOMA LUNG CANCER PATIENTS IN KUALA LUMPUR, MALAYSIA - Bangash, Nida Sajid Ali; Hashim, Natasha; Ismail, Nahlah Elkudssiah (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Adenocarcinoma (AC) of the lung is now the most common histologic type of non-small cell lung cancer (NSCLC) worldwide since the past 20 years. This study was conducted to investigate survival difference among smoker and non-smoker lung AC patients. Methods: A retrospective observational study was conducted for 81 advanced NSCLC adult Malaysian patients in Radiotherapy and Oncology Clinic at Hospital Kuala Lumpur, Malaysia. A total of adult 30 Malaysian smokers and 51 non-smokers with lung AC were included. Ex-smokers were not included in the study. Demographic and clinical data were collected and described. For survival analysis, Kaplan–Meier test and log-rank test were used to calculate overall survival (OS) and analyse the difference in the survival curve. Cox proportional hazard model was used to identify prognostic significance of smoking status. Results: Non-smokers showed a significant association with female gender and Stage IV NSCLC. The median OS was higher for non-smokers (493 days) as compared to smokers (230 days). The Cox proportional hazard model showed higher hazard ratio for smokers. Conclusion: Non-smoking is an independent positive prognostic factor in lung AC.